Pengaruh Brand Experience Terhadap Keputusan Pembelian Melalui Kepuasan Konsumen Sebagai Variabel Intervening Pada E-Commerce Shopee Di Kota Denpasar (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
This research is conducted in Denpasar City with the intention of discovering how customer happiness on Shopee affects brand experience and, by extension, purchase choices. This research used a quantitative technique. This research uses a non-probability sampling approach called purposive sampling to collect data from 65 participants drawn from the population of Denpasar City who use Shopee e-commerce. The actual number of users is unknown, but it is infinite. This research used SmartPLS 3.0 as its analytic tool. This research found that consumers' positive and statistically significant experiences with brands influenced their purchase choices. There is a favourable and statistically significant relationship between customer happiness and brand experience. There is a positive and statistically significant relationship between customer satisfaction and purchase behaviour. Additionally, customer happiness, as a result of a pleasant brand experience, significantly influences purchase choices. This research concludes that in order to keep users engaged and encourage them to make more purchases on Shopee, the e-commerce platform must keep improving and introducing new features.